Quantum Mechanics and Relational Realism: Logical Causality and Wave Function Collapse - Epperson, Michael (Process studies, 2009)
By the relational realist interpretation of wave function collapse, the quantum mechanical actualization of potentia is defined as a decoherence-driven process by which each actualization (in "orthodox" terms, each measurement outcome) is conditioned both by physical ana logical relations with the actualities conventionally demarked as "environmental" or external to that particular outcome. But by the relational realist interpretation, the actualization-in-process is understood as internally related to these "enironmental" data per the formalism of quantum decoherence. The concept of "actualization via wave function collapse" is accounted for solely by virtue of these presupposed logical relations—the same logical relations otherwise presupposed by the scientific method itself—and thus requires no "external" physical-dynamical trigger: e.g., the Gaussian hits of GRW, acts of conscious observation, etc. By the relational realist interpretation, it is the physical and logical relations among quantum actualities (quantum "final real things") that drives the process of decoherence and, via the latter, the logically conditioned actualization of potentia. In this regard, the relational realist interpretation of quantum mechanics is a praxiological interpretation; that is, these physical and logical relations are ontobgically active relations, contributing not just to the epistemic coordination of quantum actualizations, but to the process of actualization itself.